Hubungan Keterampilan Koping dan Empati Terhadap Kesehatan Mental Remaja di SMA - Tiara Alya Fauziyah; David Tjahyadi (Jayapangus Press, 2026)
Adolescence is a vulnerable developmental period marked by increased risk of mental health problems. Coping skills and empathy are important psychological factors that may influence adolescent mental well-being. This study examined the relationships among coping skills, empathy, and mental health among high school students using a cross-sectional quantitative design with 152 participants. Data were collected using the Brief COPE, Basic Empathy Scale (BES), and Self-Reporting Questionnaire-20 (SRQ-20), and analyzed using Pearson correlation. Findings indicated that adaptive coping skills were significantly associated with fewer symptoms of emotional mental disorders. In contrast, empathy showed a significant positive correlation with mental disorder symptoms. This paradoxical finding suggests that while empathy is socially beneficial, high levels of empathy may increase psychological vulnerability when not accompanied by adequate emotional regulation. These results highlight the importance of strengthening adaptive coping strategies while simultaneously fostering balanced empathy supported by emotional regulation skills in adolescent mental health interventions.